Source Base of Religious History of Podillia Region (End of the XVIII – Beginning of the XX Century) - Blazhevych, Yurii (Pedagogical Discourse, 2013)
The article highlights the main ideas and experience of usage of significant number of archival and documentary materials of domestic and foreign public archives on religious history of Podillia region in the end of the XVIII – beginning of the XX century during so-called imperial period, when the Right-Bank Ukraine and Podillia region were incorporated into the Russia. Considerable attention is given to analysis of the collections 127, 5422 , 533 of the Central State Historical Archive of Ukraine in Kyiv , collections 34, 64, 87, 111, 227, 228, 237, 315 , F-685 of Khmelnytskyi Regional State Archive and collections R-200 , D-375 , D-513, 506, 546 , D-606 , D-789 , D-799 of Vinnytsia Regional State Archive, collections 796, 1263, 1281, 1488 of the Russian State Historical Archive in St. Petersburg, collections 136, 295, 1781, 3245 of the National historical Archive of Belarus in Minsk.